Pengaruh Penambahan Minyak Sacha Inchi dan Ekstrak Bunga Telang Terhadap Kandungan Omega-3 dan Antioksidan Produk Mie Untuk Diabetes - Syalwa Destrianti Sukma Sukma; Asysyfa Riana; Yuliati Widiastuti; Agus Triyono; Hari Hariadi (Universitas Muhadi Setiabudi, 2026)
Wheat flour-based noodles have a high glycemic index and low fiber content, making them less suitable for individuals with diabetes. This study aimed to evaluate the effect of adding sacha inchi oil and butterfly pea extract on the omega-3 and antioxidant content of mocaf-based noodles. The research was conducted experimentally with three formulations: F1 (93% mocaf flour, 2% sacha inchi oil, and 5% butterfly pea extract), F2 (87% mocaf flour, 3% sacha inchi oil, and 10% butterfly pea extract), and F3 (81% mocaf flour, 4% sacha inchi oil, and 15% butterfly pea extract). Analyses included proximate tests, omega-3 levels, antioxidant activity, and organoleptic evaluations. Organoleptic data were analyzed using one-way ANOVA followed by Tukey’s post hoc test to determine significant differences between formulations. Univariate results showed a significant increase in omega-3 content in F1 (p<0.05), and the highest antioxidant activity was also found in F1, with a moderate antioxidant activity value. Bivariate analysis indicated a significant relationship between the addition of functional ingredients and the improvement of nutritional content and organoleptic scores. F1 was the best formulation in terms of taste and color. It was concluded that F1 is the most optimal combination. Further studies are needed to assess glycemic index and shelf life. Keywords: Diabetes mellitus, mocaf noodles, sacha inchi oil, butterfly pea, Omega-3, antioxidant